Alternative experimental methods for machine tool dynamics identification: A review - Iglesias, Alexander; Taner Tunç, L.; Özsahin, Orkun; Franco, Oier; Munoa, Jokin; Budak, Erhan (Mechanical systems and signal processing, 2022)
[Display omitted] •Dynamic characterization of machine tools is essential for machining assessment.•Traditional dynamic characterization methods have limitations with machine tools.•Alternative dynamic characterization methods overcome traditional methods.•Simple and universal method to measure dynamic response for machine tools needed. An accurate machine dynamic characterization is essential to properly describe the dynamic response of the machine or predict its cutting stability. However, it has been demonstrated that current conventional dynamic characterization methods are often not reliable enough to be used as valuable input data. For this reason, alternative experimental methods to conventional dynamic characterization methods have been developed to increase the quality of the obtained data. These methods consider additional effects which influence the dynamic behavior of the machine and cannot be captured by standard methods. In this work, a review of the different machine tool dynamic identification methods is done, remarking the advantages and drawbacks of each method.